Watermelon Production Budget for North Florida - Kevin Athearn; Marina Burani Arouca; Robert C. Hochmuth; Josh H. Freeman; Nicholas Dufault; Benjamin Broughton; Tatiana Sanchez; Luke Harlow; Henry T. Pittman; Mark Warren (EDIS)
This publication describes a sample watermelon production budget for a spring season in north Florida. We estimate costs for fixed assets, equipment operation, labor, materials, services, harvesting and marketing. We also estimate yield and potential returns. A budget summary and sensitivity table are provided. A spreadsheet that can serve as a budget template accompanies the manuscript.